2020
DOI: 10.3390/met10050652
|View full text |Cite
|
Sign up to set email alerts
|

Numerical-Experimental Correlation of Dynamic Test of a Honeycomb Impact Attenuator for a Formula SAE Vehicle

Abstract: A honeycomb impact attenuator for a Formula SAE (FSAE) prototype vehicle is examined using both experimental and numerical analyses. Two common FSAE impact attenuators were compared to a new design concept, combining four layers of hexagonal honeycomb. The comparison aimed to obtain the combination of the lowest mass and highest energy absorption. The attenuator must comply with both the FSAE championship rules and further internally-defined design constraints. The work continues addressing the numerical-exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…Thus, a number of teams purchased the product, tested, and deployed it in their car. As a matter of fact, owing to the complexity of the simulations, a few studies attempted to numerically study the crushing behavior of the honeycomb block in the scope of FS competitions [32][33][34]. An unusual IA design made from aluminum honeycomb panels and aluminum sheets was examined in [33], which met the competition requirements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a number of teams purchased the product, tested, and deployed it in their car. As a matter of fact, owing to the complexity of the simulations, a few studies attempted to numerically study the crushing behavior of the honeycomb block in the scope of FS competitions [32][33][34]. An unusual IA design made from aluminum honeycomb panels and aluminum sheets was examined in [33], which met the competition requirements.…”
Section: Introductionmentioning
confidence: 99%
“…An unusual IA design made from aluminum honeycomb panels and aluminum sheets was examined in [33], which met the competition requirements. For purposes of FS competition, in [34], an aluminum honeycomb IA was examined and compared with a hollow truncated thin-walled pyramid and a hybrid IA made from honeycomb panels bonded to several CFRP plates. It was found that all designs met FS requirements and the hybrid IA was the lightest and the most energy-absorbing.…”
Section: Introductionmentioning
confidence: 99%
“…The uniform-tandem honeycombs with separators have been found to exhibit superior energy absorption capabilities when compared to single-layer honeycombs. [47][48][49][50] However, it is important to note that the deformation sequence of uniform-tandem honeycomb structures is unpredictable due to potential manufacturing imperfections. The gradient strategy is used to deal with imperfections in the tandem honeycomb structure.…”
Section: Introductionmentioning
confidence: 99%
“…Lightweight sandwich structures with lattice cores [1,2] and foam cores [3,4] have been widely studied and applied due to their outstanding mechanical performance [5][6][7]. Lattice cored structures such as pyramidal [8,9], corrugated [10,11], Kagome [12], and honeycomb cores [13][14][15] have advantages in load carrying applications; however, after the loading force reaches its peak, core member softening occurs and leads to an immediate and dramatic decline of load-carrying capacity [8]. In contrast, foam structures have excellent energy absorption properties [16][17][18] and functional designs, such as acoustic absorption [19,20] and thermal insulation [21,22], but their mechanical strength is limited due to the microstructure of the core and defects during the foaming process and high porosity [23].…”
Section: Introductionmentioning
confidence: 99%